Effects of rehabilitation in patients with cardiac disease - Taylor, Ann Elizabeth (1996)
Prospective, randomised controlled trials were performed to investigate the benefits of cardiac rehabilitation in two selected patient groups. One group comprised patients in the early stage of recovery after an uncomplicated myocardial infarction. The other consisted of patients with stable chronic heart failure, who are usually excluded from exercise programmes.